Kualitas Pelayanan Publik di Puskesmas Peneleh Kota Surabaya - Sunardi, Devy Septiani (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Initial observation showed that the quality of service at Puskesmas Peneleh Surabaya was less than optimal. As a means of public health service providers, puskesmas should practice quality service that is based on ServQual concept. The purpose of this research is to know and describe about the quality of public services in Peneleh Health Center Surabaya and to know and describe the supporting and inhibiting factors in public service at Peneleh Public Health Center Surabaya. Data analysis method used in this research is interactive model from Miles and Huberman. The results showed that the quality of public services in Peneleh Public Health Center is not maximal overall. This is because of the five elements of public service quality in Peneleh Puskesmas, there are two elements that are less than the maximum, namely the element of responsiveness (responsiveness) and empathy (empathy). In addition, the results of the study indicate that the supporting factors of public service at Peneleh Public Health Center of Surabaya consist of: the government fully supports all health facilities in Puskesmas Peneleh so that the development of health can run maximally, there is harmony of relationship between staff Peneleh Puskesmas and patient and number doctors at Puskesmas Peneleh are considered sufficient in the need for services for patients. While the inhibiting factor of public service at Puskesmas Peneleh Kota Surabaya consist of: employees or staff of drug or pharmacy is considered less in terms of quantity, the existence of employees in the pharmacy who are considered less responsive and dexterous in providing drug services to patients and the condition of shortage of drugs in pharmacy section. Â Keywords: public service, community satisfaction, and puskesmas